2021
DOI: 10.47933/ijeir.883510
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Hole Shape Effect on Static Analysis of Perforated Plates With Staggered Holes

Abstract: In this paper, a series of analysis with finite element method was carried out with varying hole shapes of perforation as well as plate dimensions. Eight different models about holes that number of edges at the hole is four to infinite namely circular holes was presented. Than the analyze results of these models with different boundary conditions as fixed supported and simply supported at four edges were compared. In this study it has shown that when the number of edges for a hole is infinite, in other words w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…[9][10][11][12][13]. Thus, in [14][15][16][17][18][19] using the finite element method, it was found that the shape of the perforation holes of the parts affects the value and nature of the distribution of equivalent stresses. The influence of the parameters of hexagonal, round and ellipsoidal holes was investigated in the works.…”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11][12][13]. Thus, in [14][15][16][17][18][19] using the finite element method, it was found that the shape of the perforation holes of the parts affects the value and nature of the distribution of equivalent stresses. The influence of the parameters of hexagonal, round and ellipsoidal holes was investigated in the works.…”
Section: Methodsmentioning
confidence: 99%